DEVELOPMENT OF THE PERMATA POMAA MODEL TO IMPROVE APPETITE AND REDUCE STUNTING IN TODDLERS TOWARDS A STUNTING-FREE ACEH - Eka Sutrisna; Husna Maulida; Yunita Sari; Yusnidar (RADJA PUBLIKA, 2024)
Stunting is a health problem that occurs due to chronic malnutrition in toddlers so that the child's weight and height do not match their age. Efforts to overcome stunting can be done by developing the